STRATEGI PEMBINAAN AKHLAK PESERTA DIDIK BERBASIS NILAI ISLAMI DI MADRASAH ALIYAH SYEKH YUSUF - Ayrin A, Hikmah; Putri Z, Nanda; Suban, Alwan (Department of Islamic Education Management, 2026)
This study aims to analyze the strategy of moral development of students based on Islamic values at Madrasah Aliyah Sheikh Yusuf. The research uses a descriptive qualitative approach to photograph the phenomenon of character development naturally. Data was collected through in-depth interviews with Akidah Akhlak teachers and homeroom teachers as primary sources, as well as literature studies as secondary sources. Data analysis is carried out interactively through reduction, presentation, and conclusion drawn. The results of the study show that the strategy of moral development is applied through four pillars: teacher example (uswah hasanah), habituation of Islamic values in madrasah culture, continuous supervision to bridge cognition and moral action, and personal approach of homeroom teachers to touch the emotional aspects of students. The findings also reveal that the internalization of values is still hampered by the influence of social media and diverse family backgrounds. This study concludes that the success of moral development requires synergy across madrasah elements and consistency of supervision. The implications of the research emphasize the importance of adaptive strategies to technological developments to strengthen the moral resilience of students.